Phase IIa study of the CD19 antibody MOR208 in patients with relapsed or refractory B-cell non-Hodgkin's lymphoma. (9th February 2018) - Jurczak, W; Zinzani, P L; Gaidano, G; Goy, A; Provencio, M; Nagy, Z; Robak, T; Maddocks, K; Buske, C; Ambarkhane, S; Winderlich, M; Dirnberger-Hertweck, M; et al.
Abstract: Background: This two-stage, phase IIa study investigated the antitumor activity and safety of MOR208, an Fc-engineered, humanized, CD19 antibody, in patients with relapsed or refractory (R-R) B-cell non-Hodgkin's lymphoma (NHL). CD19 is broadly expressed across the B-lymphocyte lineage, including in B-cell malignancies, but not by hematological stem cells. Patients and methods: Patients aged ≥18 years, with R-R NHL progressing after ≥1 prior rituximab-containing regimen were enrolled into subtype-specific cohorts: diffuse large B-cell lymphoma (DLBCL), follicular lymphoma (FL), other indolent (i)NHL and mantle cell lymphoma (MCL). Treatment was MOR208, 12 mg/kg intravenously, weekly, for 8 weeks. Patients with at least stable disease could continue treatment for an additional 4 weeks. Those with a partial or complete response after 12 weeks could receive extended MOR208 treatment (12 mg/kg, either monthly or every second week) until progression. The primary end point was overall response rate. Results: Ninety-two patients were enrolled: DLBCL ( n = 35), FL ( n = 34), other iNHL ( n = 11) and MCL ( n = 12). Responses were observed in DLBCL, FL and other iNHL cohorts (26%, 29% and 27%, respectively). They lasted ≥12 months in 5/9 responding patients with DLBCL, 4/9 with FL and 2/3 with other iNHL. Responses in nine patients are ongoing (>26 months in five instances). Patients with rituximab refractory disease showed a similar response rate and progression-free survival time to patients with non-refractory disease. The most common adverse events (any grade) were infusion-related reactions (12%) and neutropenia (12%). One patient experienced a grade 4 infusion-related reaction and eight patients (9%) experienced grade 3/4 neutropenia. No treatment-related deaths were reported. Conclusions: MOR208 monotherapy demonstrated promising clinical activity in patients with R-R DLBCL and R-R FL, including in patients with rituximab refractory tumors. These efficacy data and the favorable safety profile support further investigation of MOR208 in phase II/III combination therapy trials in R-R DLBCL. ClinicalTrials.gov number: NCT01685008.